GROUNDS FOR LIMITATION OF LABOR RIGHTS OF EMPLOYEES REGARDING PROTECTION OF PERSONAL DATA UNDER CONDITIONS OF MARITAL STATE - Khlystun, Yuliia; Davydenko, Daria (Archives of Criminology and Forensic Sciences, 2023)
Abstract: the specified article examines personal data, their list, their extension to labor relations, definition of martial law is disclosed and the grounds for limiting the rights and freedoms of a person and citizen, their legal regulation, grounds for processing and guarantees for the protection of personal data of employees in the conditions of martial law are defined. It is noted that the personal data of an employee is a narrower concept than the personal data of a person and in connection with the lack of legal protection regulation of personal data of employees while their processing and protection, there are urgent issues that require legal regulation specifically by special legislation, which should be adopted from taking into account practice of ECHR and European experience. In addition, in Ukraine, the employer is not obliged to obtain consent from its employees for processing of their personal data, provided that the employee’s personal data (for example, name, patronymic and surname of the employee, information about education, marital status) is used by the employer for exercising the rights and fulfilling owner duties in the field of labor relations in accordance with the law with provision of appropriate protection. It was concluded that employee’s personal data in wartime, in particular in the occupied territories, are not protected, and require more detailed protection from both State and employers.